1996
DOI: 10.1007/bf02027955
|View full text |Cite
|
Sign up to set email alerts
|

Intrapopulational changes in sex pheromone composition during scotophase in oriental tobacco budworm,Helicoverpa assulta (Guenée) (Lepidoptera: Noctuidae)

Abstract: Solvent extracts of individual pheromone glands were prepared from femaleHelicoverpa assulta (Guenée) at 2-hr intervals throughout the scotophase. The amounts of female sex pheromone components, (Z)-9-hexadecenal, (Z)-11-hexadecenal, (Z)-9-hexadecenyl acetate, and (Z)-11-hexadecenyl acetate, in the extracts were determined by gas chromatographic analysis. Although females called from early scotophase (2 hr) until late scotophase (6 hr) the quantity of extracted pheromone remained high at 8 hr, the end of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Natural hybrids between these species have never been found in the field. Prezygotic isolation mechanisms probably play a potential role in preventing gene flow between two species (Wu et al, 1990;Park et al, 1996;Liu et al, 1994;Chen, 1999). The host-plant range of the two species is quite different.…”
Section: Discussionmentioning
confidence: 99%
“…Natural hybrids between these species have never been found in the field. Prezygotic isolation mechanisms probably play a potential role in preventing gene flow between two species (Wu et al, 1990;Park et al, 1996;Liu et al, 1994;Chen, 1999). The host-plant range of the two species is quite different.…”
Section: Discussionmentioning
confidence: 99%
“…The variation could have been caused by collection of experimental insects from different areas. An approximately opposite ratio (7:100) of the two components was produced by females of H. assulta in China as their sex attractant pheromone (Liu et al, 1994) and this ratio was shown to vary with insect distribution and the pheromone release times in a light-dark cycle, but Z9-16:Ald was always a dominant component (Cork et al, 1992;Park et al, 1996). With species-specific ratios of the same sex pheromone components, these closely related species achieve reproduction isolation.…”
Section: Introductionmentioning
confidence: 94%
“…Relative amounts of Z11 and Z9-16:OAc found in the pheromone gland of H. assulta were even much higher than that of the corresponding aldehydes ( Table 2). The two acetates were identified as the sex pheromone components in a Korean population (Park et al, 1996), but not in the Chinese strain (Liu et al, 1994). In the pheromone gland of the hybrid, the ratio of Z9-16:Ald to Z11-16:Ald was determined as 4.0:100.…”
Section: Differences In Sex Pheromone Composition In H Armigera H mentioning
confidence: 99%
“…It was then found that an egg parasitoid Trichogramma chilonis was attracted to (Z)-11-hexadecenyl acetate (Z11-16:Ac), one of the sex pheromone components in a Korean population of H. assulta (Boo and Yang, 2000), leaving us the question whether the acetate plays the same role in Japan, China and Thailand because this compound is not present or is behaviorally inactive in H. assulta in these countries. In a Korean population, the ratios of the two acetate isomers, Z9-16:Ac and Z11-16:Ac, to the corresponding aldehyde isomers gradually changed in female H. assulta during the scotophase (Park et al, 1996). But, a small-scale field experiment showed that effective mating disruption for H. assulta could be achieved in a Korean hot pepper field with the Korean pheromone composition (Park et al, 1999).…”
Section: The Oriental Tobacco Budwormmentioning
confidence: 99%